2021
DOI: 10.1371/journal.pgen.1009890
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase 1 controls cardiomyocyte proliferation during embryonic heart development and cardiac regeneration in zebrafish

Abstract: In contrast to mammals, the zebrafish maintains its cardiomyocyte proliferation capacity throughout adulthood. However, neither the molecular mechanisms that orchestrate the proliferation of cardiomyocytes during developmental heart growth nor in the context of regeneration in the adult are sufficiently defined yet. We identified in a forward genetic N-ethyl-N-nitrosourea (ENU) mutagenesis screen the recessive, embryonic-lethal zebrafish mutant baldrian (bal), which shows severely impaired developmental heart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 46 publications
(61 reference statements)
0
11
0
Order By: Relevance
“…Moreover, acetylation of vestigial-like 4 (VGLL4) at K225 by P300 negatively regulates its binding to the transcription factor TEA Domain Transcription Factor 1 (TEAD1), leading to decreased neonatal cardiomyocytes proliferation and cardiomyocytes necrosis [ 20 ]. Inhibition of HDAC1 was also described to decrease the proliferation cardiomyocyte in zebrafish [ 49 ]. Indeed, mutation in HDAC1 gene that induces protein instability is associated with decreased cardiomyocyte proliferation, suggesting an important role of HDAC1 during heart growth [ 49 ].…”
Section: Cardiac Acetylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, acetylation of vestigial-like 4 (VGLL4) at K225 by P300 negatively regulates its binding to the transcription factor TEA Domain Transcription Factor 1 (TEAD1), leading to decreased neonatal cardiomyocytes proliferation and cardiomyocytes necrosis [ 20 ]. Inhibition of HDAC1 was also described to decrease the proliferation cardiomyocyte in zebrafish [ 49 ]. Indeed, mutation in HDAC1 gene that induces protein instability is associated with decreased cardiomyocyte proliferation, suggesting an important role of HDAC1 during heart growth [ 49 ].…”
Section: Cardiac Acetylationmentioning
confidence: 99%
“…Inhibition of HDAC1 was also described to decrease the proliferation cardiomyocyte in zebrafish [ 49 ]. Indeed, mutation in HDAC1 gene that induces protein instability is associated with decreased cardiomyocyte proliferation, suggesting an important role of HDAC1 during heart growth [ 49 ].…”
Section: Cardiac Acetylationmentioning
confidence: 99%
“…This Brg1 gene was specifically found to regulate HDAC mechanisms through development [ 73 ]. In zebrafish, it has been found that the histone deacetylates 1 (HDAC1) is conserved in zebrafish and plays a vital role in the regeneration and proliferation of cardiomyocytes similar to that of neonatal and embryonic mammalian cardiomyocytes [ 74 ]. Finally, it has been observed that by inhibiting HDACs, such as HDAC2, has helped with cardiac repair after injury by specifically inhibiting increased cardiac cell autophagy [ 75 ].…”
Section: Epigenetic Regulation Of Cardiomyocytes Through Developmentmentioning
confidence: 99%
“…Zebrafish studies have revealed that hdac1 is involved in SHF heart development and adult cardiac regeneration (18,19). In zebrafish, hdac1 mutants have less cardiomyocytes (CMs) in the ventricle while inhibition of hdac1 (and other class I HDACs) reveal reduced proliferation during regenerative events (18,19,20,21). Zebrafish hdac1 mutants are embryonic lethal, similar to the mouse models, but MZsap130a mutants are viable as adults suggesting that hdac1 and sap130a may have distinct functions in zebrafish cardiogenesis (18,22).…”
Section: Introductionmentioning
confidence: 98%
“…HDACs have been reported to regulate many aspects of development, including cardiac development in zebrafish, mouse, and chick models, evidenced by treatment with a pan HDAC small molecule inhibitor, Trichostatin A (14,15,16,17). Zebrafish studies have revealed that hdac1 is involved in SHF heart development and adult cardiac regeneration (18,19). In zebrafish, hdac1 mutants have less cardiomyocytes (CMs) in the ventricle while inhibition of hdac1 (and other class I HDACs) reveal reduced proliferation during regenerative events (18,19,20,21).…”
Section: Introductionmentioning
confidence: 99%